2014
DOI: 10.1155/2014/343497
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Solution of Nonlinear Sine-Gordon Equation by Modified Cubic B-Spline Collocation Method

Abstract: Modified cubic B-spline collocation method is discussed for the numerical solution of one-dimensional nonlinear sine-Gordon equation. The method is based on collocation of modified cubic B-splines over finite elements, so we have continuity of the dependent variable and its first two derivatives throughout the solution range. The given equation is decomposed into a system of equations and modified cubic B-spline basis functions have been used for spatial variable and its derivatives, which gives results in ame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 21 publications
3
29
0
Order By: Relevance
“…The L ∞ and RMS norms at the different time levels are shown in Table 2. From Table 3, it can be observed that the MCB-DQM results are better than the results obtained in [17,18,20]. Fig.…”
Section: Numerical Results and Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…The L ∞ and RMS norms at the different time levels are shown in Table 2. From Table 3, it can be observed that the MCB-DQM results are better than the results obtained in [17,18,20]. Fig.…”
Section: Numerical Results and Discussionmentioning
confidence: 70%
“…Dehghan & Shokri [14] 0.25 2.43 6 10 − × 5.46 6 10 − × 1.18 5 10 − × 2.32 5 10 − × 3.91 5 10 − × 5.89 6 10 − × 0.50 5.54 6 10 − × 7.39 6 10 − × 4.19 5 10 − × 4.11 5 10 − × [14], and Mittal & Bhatia [20]. Table 5 shows the 2 L and L ∞ error norms at the different time levels, quantatively.…”
Section: Numerical Results and Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In this work, we present the differential quadrature method based on modified cubic B-spline basis functions(as used in [7], [23]), to solve some one dimensional non-linear wave equations. The wave equation is converted into system of partial differential equations and then equations are discretized spatially by modified cubic B-spline functions based differential quadrature method.…”
Section: Introductionmentioning
confidence: 99%